Relationships, expertise, incentives, and governance: supporting care home residents' access to health care: an interview study from England - Goodman, Claire; Davies, Sue L.; Gordon, Adam L.; Meyer, Julienne; Dening, Tom; Gladman, John R.F.; Iliffe, Steve; Zubair, Maria; Bowman, Clive; Victor, Christina; Martin, Finbarr C. (Elsevier, 2015)
Objectives To explore what commissioners of care, regulators, providers, and care home residents in England identify as the key mechanisms or components of different service delivery models that support the provision of National Health Service (NHS) provision to independent care homes.